ANALISIS VALIDITAS PENGEMBANGAN MEDIA PEMBELAJARAN PAPIN (PAPAN PINTAR) MATERI SIMBOL SILA-SILA PANCASILA KELAS II UPT SDN 1 KARAS - Lusi Anggi Anggraeni; Mardi Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the validity or feasibility of the PAPIN (Smart Board) learning media designed for Pancasila principles material for second-grade students in elementary schools. Research and Development is the method used in this study, while ADDIE is the model used in the research and development process. The validators entrusted with the validation process are language experts, subject matter experts, and media experts. The results of the validation process indicate that the PAPIN (Smart Board) media achieved a validity score of 92.7% from the subject matter expert, 96% from the language expert, and 80% from the media expert. The average validity score reached 89.5%, which falls within the “valid” category. Therefore, the PAPIN (Smart Board) media is suitable for use in educational activities.